Experimental study on the mechanical properties and consolidation mechanism of microbial grouted backfill - Xuejie Deng; Yu Li; Fei Wang; Xiaoming Shi; Yinchao Yang; Xichen Xu; Yanli Huang; Benjamin de Wit (International Journal of Mining Science and Technology, 2022)
Backfill mining technology is the practice of returning waste materials underground for both disposal and geotechnical stability, however, a challenge with current technologies is that they commonly require cement-based binders which have a relatively high environmental impact. Finding alternatives to cement-based binders can improve environmental performance and this paper proposes microbial grouted backfill (MGB) as a potential solution. In this paper, the effects of the cementation solution concentration (CSC), volume ratio of bacterial solution to cementation solution (VRBC), particle sizes of the aggregates, and the number of grouting batches on the mechanical properties of MGB are studied. The experimental results show that MGB strength increased, up to a peak value, as CSC was increased, before decreasing as CSC was increased further. The results also show that MGB strength increased, up to a peak value, as VRBC decreased, before decreasing as the VRBC was decreased further. The peak strength was achieved at a CSC of 2 mol/L and a VRBC of 1:9. The strength of the MGB also increased as the number of grouting batches increased. Graded MGB samples showed the highest UCS, 25.12 MPa, at particle sizes of 0.2 to 0.8 mm, while full (non-graded) MGB samples displayed mean UCS values ranging from 1.56 MPa when the maximum particle size was 0.2 mm, up to 13 MPa when the maximum particle size was 1.2 mm. MGB samples are consolidated by the calcium carbonate that is precipitated during microbial metabolism, and the strength of MGB increases linearly as calcium carbonate content increases. The calcium carbonate minerals produced in MGB materials are primarily calcite, with secondary amounts of vaterite.